Mixture of Faults Identification on Power Transformers Using Multi-Method Dissolved Gas Analysis - Prasojo, Rahman Azis; Muhammad Akmal Afibuddin Putra,; Neelmani, (International Journal of Frontier Technology and Engineering, 2022)
Utilities rely on the various Dissolved Gas Analysis (DGA) interpretation methods to identify incipient fault within power transformers. However, confusion often arises due to the use of different DGA methods which can have different results or fail to detect mixture of faults (multiple faults). This paper implements the combination of Duval Triangle and Duval Pentagon as one of the most consistent methods to do fault identification based on DGA. Recent historical DGA data of generator step up high voltage power transformers and other several previously published historical data were collected and analyzed. This article aims to assist transformer asset manager in detecting mixture of faults using multi method. The use of combined Duval triangle and Pentagon method is done in accordance to the guideline in IEEE C57.104-2019.